Purification of Timor’s Genoak (Acorus calamus ) Essential Oil using Reduced Pressure Distillation - Henci, Rensy A; da Cunha, Theo; Ishaq Lerrick, Reinner (Universitas Nusa Cendana, 2019)
A research about Asaron oil purification produced over Stahl distillation has been done. This research was conducted by distillation of Genoak’s roots, rhizomes and leaves whilst the purification was carried out through reduced pressure distillation. A yellowish oil was yield respectively 1,83 gram from the roots and rhizomes and 1,26 gram from leaves which then was revealed as 90,49% pure of asaron confirmed using GC-MS, 1H-NMR and FT-IR analysis.